Bias Gender dalam Keluarga - Setiawati, Setiawati (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2018)
Research on gender bias in the family (A Study in Padang Complex Singgalang) aims to reveal whether there is gender bias in the family in Padang Singgalang complex, especially in terms of implementation of the family in domestic chores, economic factors or family income and family decision making. This research is a family Sabjek dikompleks Singgalang (mothers and fathers) of which withdrawals are "Snow Sampling Boal." The approach of this research is a qualitative approach, because the behavior of daily life in the family is a cultural event and should use a qualitative approach, and this kind of research classified as a case study. The data collection techniques used were interviews and participatory observation, while analysis of data by using the "interpretive Uderstanding". The results can be summarized as follows: (1) In implementing the family domestic work, there have been kecederungannya collaboration between husband and wife, in this case the husband has been carrying out domestic work, although limited to certain jobs fatherly. However, the participation of the husband, not because of their responsibilities within the family, but because his wife wanted to help ease the job. This means there is still gender bias in the family, especially mengkotakkan work between men and women. (2) The role of mothers in the family economy in the family economy provides a substantial contribution, even among those who earn more than their husbands, but the presence of tersebutmasih permanent income defined as the additional revenue. This recognition not only by their husbands, but also the opinions of these mothers. (3) In making decisions, it seems there has been cooperation between the husband and wife, but the things which ranges around the daily needs of the domestic like procurement, the issue of household appliances, clothing problems of children and so forth, it was entirely in the hands of the istri.Jadi thus still there is gender bias in the research area of decision making.